The negative effects of the pandemic on human behavior; alienation and social anhedonia: the example of sport sciences students - Mehmet H. Akgül; Nedim Tekin (IP Iermakov S.S., 2022)
Background and Study Aim. The social change brought about by the pandemic process all over the world has led to the restructuring of human behavior and daily life practices. This process has brought with it some social-psychological problems (such as alienation and social anhedonia) for social segments. For this reason, the aim of the research is to examine the alienation and social anhedonia levels of the students studying at the faculty of sport sciences during the pandemic process. Material and Methods. The sample of the research consists of students studying at the faculties of sport sciences of different universities in Turkey. A total of 423 students (271 males, 152 females) participated in the study. Due to the normal distribution of the data, the t-test, one of the parametric tests, was performed for paired groups, and the relationship between Social Anhedonia Scale and Alienation Scale sub-dimensions was tested with Pearson correlation analysis. Statistical analyzes were performed with the "Statistical Package for the Social Sciences" commercial software (SPSS for Windows, version 26.0, SPSS). The significance level was determined as p<0.05 in the analyzes, and skewness and kurtosis values were considered for the normality analysis. Results. According to the results obtained, it can be said that the pandemic process negatively affected the social anhedonia and alienation levels of male students studying at the faculty of sport sciences compared to female students. Again, it is seen that the level of alienation of the students who do sports at the professional level is higher than the students who do sports at the amateur level. Similarly, it is seen that the students of the faculty of sport sciences dealing with team sports have higher levels of social isolation, which is one of the sub-dimensions of the alienation scale, compared to the students who are engaged in individual sports. Finally, there is a negative and low-level significant relationship between social anhedonia and alienation scale sub-dimensions (p<0.05; r=-0.187; r=-0.164; r=-132). Conclusions. As a result, it can be said that the pandemic process has had similar negative effects on the students studying in the faculties of sport sciences, as in other social segments.